Modeling the causal linkages between transport, economic growth and environmental degradation for 75 countries. (June 2017) - Saidi, Samir; Hammami, Sami
Highlights: We study the causality between transport, growth and environment for 75 countries. We divide the global panel into 3 sub-panels; high, middle, and low-income panel. Bidirectional causality exists between transport and growth for the three sub-panels. Transport and growth affect the environment in the middle and low-income panels. Abstract: This article investigates the causal relationships between freight transport, economic growth and environmental degradation for 75 countries over the period 2000–2014. Based on the income level of countries, we divide the global panel into three sub-panels; namely, high-income, middle-income and low-income panel. The distinction between panels allows the employing of dynamic panel data models in simultaneous-equations estimated by the Generalized Method of Moments. The main results note the existence of feedback effect among income and transport. For the high-income panel, a bi-directional causality exists between environmental degradation and economic growth and a unidirectional causality goes from transport to environmental degradation. The results give the same findings for the middle and low-income panels where we found an environmental degradation mainly affected by economic growth and freight transport while, in the reverse direction, the effect is weak and statistically insignificant. This empirical evidence supports strongly the coupling relationship between economic growth and freight transport, but rejects the feedback effect between environmental degradation and economic growth for the middle and low-income countries.